Calcio, media e formazione tra professionismo ed età giovanile. Dalla carta al web, ai social media, riflessioni sul caso fiorentino - Di Bari, Cosimo (Studi sulla Formazione/Open Journal of Education, 2023)
The paper reflects on the training potential of soccer - addressing both professional and youth activities - and investigates the way in which the media have represented (during the 20th century) and represent (today) soccer, emphasizing how narratives and discourses about soccer produce both formative potentials as much as troubling outcomes that can overshadow the authentic values of the sport. The task of pedagogy is precisely to highlight the risks and opportunities of these representations and to promote, in all the actors involved, active attitudes to ensure that soccer, even today, can create opportunities to promote self-care, of the other and of the world.